ELECTRONIC PORTABLE ARTICULATION MIRROR (EPAM): MEDIA UNTUK MENINGKATKAN BAHASA MIMIK ANAK TUNARUNGU - Burnyanuddin, Erbi; Bowo, Doni; Junianto, Rizki (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractCommunication is a fundamental human need to interact with each other. Forchildren with special needs, particularly children with hearing impairment, communicationbecomes very important because they must learn to communicate harder thanthe normal ones. In Karnna Manohara Special School an articulation mirror is used asa device to train children with hearing impairment in communication, especially interms of facial expressions. Unfortunately, however, the device is less effectivebecause it is large and not portable. The purpose of this program is to implementElectronic Portable Articulation Mirror (EPAM) which is a modification of a largemirror articulation into a portable, practical and more effective one. This program isconducted through several steps, namely observation, device improvement, feasibilitytest (calibration), evaluation and revision, application of device, and evaluation. Theresults of this program is EPAM design that consists of a mirror, an LCD display, acontrol menu, sound indicator light, power indicator light, power button, displaybaterray checker, 3.5 mm audio port, audio port 7 mm, charger port, speakers,headsets, and microphone. The implementation of EPAM in speech therapy businessunit of Karnna Manohara Special School has succeeded in increasing the facialexpressions of the deaf children with the gain of 0.72 and increasing the capacity witha high criterion.